Prevention of Adverse Sexual Behavior Through the Curriculum Model of Social Reconstruction with Religious Characters - Amir Mahrudin; Asmil Ilyas; Megan Asri Humaira (Universitas Djuanda, 2020)
This study aimed to analyze the application of the social reconstruction curriculum of a religious character in preventing deviation of adolescent sexual behavior. The research method used is the quantitative method, where data collection is done by systematic observation. This study shows that adolescent sexual behavior can be categorized into three, namely adolescent sexual behavior that is healthy, unhealthy, and deviant. In addition, the application of a social reconstruction curriculum of religious character is considered effective in preventing deviant adolescent sexual behavior. This is due to the implementation of religious values in the prevention process.